(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
A poet’s heart is as wide as a dash, as high as a mountain, as a flood as a river. Only poets can express the momentary sufferings and joys of the human soul in lines. In any genre of the most delicate literary genre, no matter how the pen is moved, the tender feelings that wave in the human heart are praised. In particular, the same can be said about the ballads, which are distinguished by their plot.